Can gesture observation help people with aphasia name actions?. (February 2020) - Murteira, Ana; Nickels, Lyndsey
Abstract: It has been suggested that gesture can play a role in the treatment of naming impairments in aphasia, however investigation is still sparse, especially when compared to research on verbal treatments. Critically, previous studies have included either verbal or gesture production in the training. However, while in speakers without language impairment, action naming is facilitated by gesture observation, no study has yet systematically determined whether gesture observation alone influences word retrieval in people with aphasia. This is the aim of the research presented here. In a gesture priming experiment, participants with aphasia named actions that were preceded by the observation of videos of congruent or unrelated gestures or a non-gesture control condition. At the group-level, action naming was facilitated by observation of congruent gestures. However, single-case analyses revealed variability in the extent to which the participants benefited from gesture cueing. The potential mechanisms underlying the effects of gesture observation on action picture naming in people with aphasia were examined by exploring participant-related and item-related predictors of improvement. It is concluded that gesture observation may facilitate verb retrieval at either semantic or lexical levels. In addition, and despite variability across individuals, gesture observation seems more likely to facilitate action naming in people with spared gesture semantics and mild-moderate deficits in lexical-semantic or post-semantic processing.